Presentation of isolated trolard vein thrombosis with subarachnoid hemorrhage: a case report and review of literature - Razmeh, Saeed; Sina, Farzad; Zaribafian, Maryam; Ghurchian, Zahra (International Journal of Research in Medical Sciences, 2016)
Cortical vein thrombosis (CVT) is uncommon and life threatening condition. It is usually secondary to the propagation of the clot from dural sinus to cortical vein, but isolated thrombosis of this vein is very rare. Usual symptoms include headache, sensory and motor deficit, seizure, confusion and an increase in intracranial pressure (ICP). Presentation with subarachnoid hemorrhage (SAH) is very rare that has been reported only in the case studies. In this paper, we describe a case of isolated trolard vein thrombosis that present with SAH.